Reflection of the Creative Personality on The Basis of The Biographical Method In Works Of Art - Adizova O.I. (Universitas Muhammadiyah Sidoarjo, 2022)
The given article reveals the expression of the writer’s personal aspects by means of biographical method. It also discusses the writers’ skill of using the biographical method and by this method justifies the existence of the information related to the writer’s biography in literary works.